The gut-lung axis in COPD: immunomodulatory roles of gut microbiota and novel therapeutic strategies - Ni, Feng-Xian; Wang, Hui-Xian; Hu, Jie; Chen, Pei-Sheng; Xu, Pan; Chen, Hui-Hui; Jiang, Ze-Bo; Huang, Dong-Hui (Frontiers in Immunology, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory disorder characterized by persistent airflow limitation and systemic inflammation, with accumulating evidence implicating gut microbiota dysbiosis as a key modulator of disease pathogenesis via the gut-lung axis. This review synthesizes current knowledge on the bidirectional communication between the gut and lungs, highlighting how microbial metabolites—particularly short-chain fatty acids (SCFAs), tryptophan derivatives, and bile acids—regulate pulmonary immunity through G-protein-coupled receptors, histone deacetylase inhibition, and aryl hydrocarbon receptor signaling. Dysbiosis-driven disruptions in these pathways exacerbate neutrophilic inflammation, impair regulatory T-cell function, and sustain TLR4/NF-κB activation, amplifying lung tissue damage and remodeling. Therapeutic strategies targeting the gut-lung axis show promise in restoring microbial homeostasis and mitigating COPD progression. Probiotics (e.g., Lactobacillus and Bifidobacterium), prebiotics (e.g., inulin), and dietary interventions (e.g., high-fiber diets) enhance SCFA production, strengthen epithelial barriers, and suppress pro-inflammatory cytokines. Advanced approaches, including fecal microbiota transplantation, nanotechnology-enabled metabolite delivery (e.g., dendrimer-complexed indole-3-acetic acid), and traditional Chinese medicine (TCM) formulations (e.g., the postbiotic formulation Qipian), demonstrate efficacy in preclinical and clinical studies by synchronizing gut-lung microbiota and inhibiting inflammatory pathways. Despite these advances, challenges remain in translating findings to clinical practice, including methodological heterogeneity, antibiotic and corticosteroid confounding, and inter-individual microbiota variability. Future research must integrate multi-omics technologies, validate biomarkers (e.g., Bacteroidales/Lactobacillus ratio, SCFA levels), and develop personalized interventions to bridge the bench-to-bedside gap. Harnessing the gut-lung axis offers transformative potential for COPD management, shifting the paradigm from symptomatic treatment to disease-modifying strategies rooted in microbiome immunology.